2011
DOI: 10.1021/es103907m
|View full text |Cite
|
Sign up to set email alerts
|

Can Natural and Virtual Environments Be Used To Promote Improved Human Health and Wellbeing?

Abstract: Exposure of individuals to natural environments, such as forests and coastlines, can promote stress reduction and assist in mental recovery following intensive cognitive activities. Settings as simple as hospital window views onto garden-like scenes can also be influential in reducing patients’ postoperative recovery periods and analgesic requirements. This paper reviews the evidence supporting the exploitation of these restorative natural environments in future healthcare strategies. The paper also describes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 26 publications
(39 reference statements)
1
88
0
1
Order By: Relevance
“…Excessive game playing in the bedroom directly disrupts sleep (Chaput et al 2014). A national survey conducted in Japan reported that the average time spent playing games among Japanese children is approximately 1.66 hrs per day, and that about 10% of Japanese children spend ≥ 4 hrs per day on game playing (National Institute for Educational Policy Research 2014), which indicates that time is shifted from sleep duration to game playing (Depledge et al 2011). Considering that toothbrushing is generally performed in the morning and at night (Murtomaa 1979;Macgregor et al 1996;McKay et al 2016), sleepdisturbed children also show a higher prevalence of dental caries, likely due to the lower frequency of toothbrushing (McKay et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive game playing in the bedroom directly disrupts sleep (Chaput et al 2014). A national survey conducted in Japan reported that the average time spent playing games among Japanese children is approximately 1.66 hrs per day, and that about 10% of Japanese children spend ≥ 4 hrs per day on game playing (National Institute for Educational Policy Research 2014), which indicates that time is shifted from sleep duration to game playing (Depledge et al 2011). Considering that toothbrushing is generally performed in the morning and at night (Murtomaa 1979;Macgregor et al 1996;McKay et al 2016), sleepdisturbed children also show a higher prevalence of dental caries, likely due to the lower frequency of toothbrushing (McKay et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…On the positive side, experience in nature, as well as outdoor exercise, have been associated with increased mental and physical well-being, as well as enhanced cognitive functioning (70). Reduced postoperative recovery times and lower analgesic requirements in hospitalized patients with access to a natural view through their room window point to a deeply seeded relationship between the natural world and the psycho-physiological dimensions of human health (71).…”
Section: Highlights Of the Recent Literaturementioning
confidence: 99%
“…Compelling evidence exists for links between contact with green space and better mental health (Depledge, Stone, & Bird, 2011), however as the literature suggests, access to green space is variable according to where you live. A survey from the Netherlands, involving 25,000 people, reported that those living within 1 km of green space were more likely to have a stronger perception of good health (Maas, Verheij, Groenewegen, De Vries, & Spreeuwenberg, 2006).…”
Section: Green Spaces and Contact To Naturementioning
confidence: 99%